Sources of funds and investment strategies of venture capital funds: evidence from Germany, Israel, Japan and the UK - Mayer, C; Schoors, K; Yafeh, Y (University of Oxford, 2001)
Using a newly constructed data set, we compare sources of funds and investment strategies of venture capital (VC) funds in Germany, Israel, Japan and the UK. Sources of VC funds differ significantly across countries, e.g. banks are particularly important in Germany, corporations in Israel, insurance companies in Japan, and pension funds in the UK. VC investment patterns also differ across countries in terms of the stage and sector of financed companies, as well as in the geographical focus of investments, and these differences are significantly related to the variations in funding sources. However, the influence of particular classes of institutions differs across countries. For example, bank backed VC firms in Germany and Japan are as involved in early stage finance as other funds in these countries, whereas in Israel and the UK they tend to invest in relatively late stage finance. While these financial institutional factors account for some of the differences in investment patterns across countries, other considerations (such as supply of entrepreneurs) are of greater significance.